2022
DOI: 10.3390/antiox11081473
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Mitochondrial Uncoupling Proteins against Age-Related Oxidative Stress in Type 2 Diabetes Mellitus

Abstract: The accumulation of oxidative damage to DNA and other biomolecules plays an important role in the etiology of aging and age-related diseases such as type 2 diabetes mellitus (T2D), atherosclerosis, and neurodegenerative disorders. Mitochondrial DNA (mtDNA) is especially sensitive to oxidative stress. Mitochondrial dysfunction resulting from the accumulation of mtDNA damage impairs normal cellular function and leads to a bioenergetic crisis that accelerates aging and associated diseases. Age-related mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 229 publications
(264 reference statements)
0
14
0
Order By: Relevance
“…UCP2 is associated with DM [ 251 ]. UCP2 may be a promising therapeutic target for treating type 2 diabetes mellitus because it regulates insulin secretion and beta-cell dysfunction [ 252 ]. Since UCP2 plays a role in reducing ROS production, the selective activation of UCP2 may have therapeutic potential in patients with diabetes [ 253 ].…”
Section: Antioxidant Activity Of Berberinementioning
confidence: 99%
“…UCP2 is associated with DM [ 251 ]. UCP2 may be a promising therapeutic target for treating type 2 diabetes mellitus because it regulates insulin secretion and beta-cell dysfunction [ 252 ]. Since UCP2 plays a role in reducing ROS production, the selective activation of UCP2 may have therapeutic potential in patients with diabetes [ 253 ].…”
Section: Antioxidant Activity Of Berberinementioning
confidence: 99%
“…Another factor correlating diabetes to AD is mitochondrial malfunctioning [ 6 , 16 , 76 ]. Mitochondrial activity is essential for normal neuronal functioning regarding ATP synthesis and for controlling calcium homeostasis [ 97 ].…”
Section: Involvement Of Diabetes In the Development Of Alzheimer’s Di...mentioning
confidence: 99%
“…Many studies confirmed that patients with impaired glucose tolerance and diabetes have an increased risk of developing Alzheimer’s disease (AD) compared to healthy individuals [ 3 , 4 , 5 ]. The association between diabetes and its effects on the development of retinopathy, neuropathy, nephropathy, and cardiovascular diseases is well established [ 6 ]. However, the underlying processes of how diabetes impacts the brain, cognition, and mental health are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 The primary function of WAT is storing triglyceride, while BAT, in contrast to WAT, dissipates the energy of chemical bindings through uncoupling protein 1 (UCP1) that results in increased fatty acid oxidation and thermogenesis. 4 , 5 Biologically active BAT can promote thermogenesis through UCP1, and activation of BAT and induction of WAT browning accelerates glycolipid uptake, and is essential for improving lipid metabolism and insulin resistance. 6 However, beige adipose tissue has the characteristics of both WAT and BAT, which can store triglyceride and promote thermogenesis after cold stimulation.…”
Section: Introductionmentioning
confidence: 99%